Effects of recombinant factor VIIa on platelet function and clot structure in blood with deficient prothrombin conversion - Carr, Marcus E., Jr.; Martin, Erika J.; Kuhn, Jan G.; Seremetis, Stephanie V. (Thrombosis and Haemostasis, 2003)
While recombinant factor VIIa (rFVIIa) shows promise as a broad-spectrum hemostatic agent, questions remain regarding the most appropriate dose and the best way to monitor its effects. In this study we tested the sensitivity of a thrombin dependent platelet assay, platelet contractile force, to the effects of rFVIIa in normal, factor-deficient, and inhibitor-containing blood samples. Dose dependent effects of rFVIIa on platelet contractile force (PCF) and clot elastic modulus (CEM) were measured in all blood samples.rFVIIa minimally affected PCF and CEM in normal blood clotted with thrombin or batroxobin. While rFVIIa minimally altered PCF and CEM in factor VIII (FVIII) deficient blood clotted with thrombin, rFVIIa increased PCF and CEM and shortened the lag phase in a dose dependent manner in batroxobin-induced clots. The effects of rFVIIa in factor IX (FIX) deficient blood mirrored the effects seen in FVIII deficient samples. Whether clotted with thrombin or batroxobin, baseline PCF and CEM were abnormally low in FVIII deficient samples containing FVIII inhibitors. In such samples, rFVIIa caused dose dependent improvement of PCF, CEM, and lag phases. In one patient with a spontaneous inhibitor, rFVIIa caused dose dependent increases in PCF and CEM in blood clotted with either enzyme.rFVIIa corrects the deficient thrombin generation seen in FVIII and FIX deficiency, and in blood containing FVIII inhibitors. As a consequence, platelet function is improved and clot structure is enhanced. Platelet contractile force and clot elastic modulus measurements are sensitive to the dose dependent effects of rFVIIa.
Keywords: Recombinant FVIIa; hemophilia; platelet contractile force; clot elastic modulus; thrombin generation